Structural and Behavioral Models of RFID-based Students Attendance System Using Model-View-Controller Pattern - Prasetyo, Koko Wahyu; Sakaria, Setiabudi (LPPM STIKI Malang, 2015)
A student attendance management system is needed by higher education institution due to the fact that the students’ attendance are one of the critical factors which decide their academic achievement. The practice of managing the attendance based on the signatures collected on papers is considered inefficient. This paper presents a set of structural and behavioral models which can be implemented as a student attendance management system which utilizes RFID technology. The ability of RFID tags to promptly deliver accurate authentication information should improve the students attendance management process efficiency. The structural and behavioral models presented in this paper are using UML class diagram and sequence diagram notations. The models are developed based on the technical architecture of model-view-controller (MVC) pattern.